Adverse Childhood Experiences and Influences on School Competency in Elementary-Aged Children - Brown, Quinlan; Comas, Meredith; Tummons, Ashley; Heasty, Reese (Kansas State University. Dept. of Sociology, Anthropology, and Social Work., 2023)
The purpose of this proposal is to study the complex associations between Adverse Childhood Experiences (ACEs) and academic competency in elementary-aged students. Our study proposes in the presence of ACEs, a disruption in a child’s normal behavioral processing occurs. This disruption then correlates with lower academic performance and behavior. Our research uses a five-year, longitudinal, cohort study. The Pediatric ACEs and Related Life Events Screener will be used to measure different levels of ACEs. Additionally, we integrate educator evaluations of academic progress by using summative and formative grade assessments to measure the level of school competency. The results of our study show the impairing nature of ACEs during early childhood, and the necessity of studying and treating ACEs at the pediatric level.
Kirmser Undergraduate Research Award - Group category, honorable mention
Keywords: Adverse Childhood Experiences (ACEs); Elementary-Aged Students; Academic Competency; Behavioral Processing; Pediatric ACEs and Related Life Events Screener